Inovasi Pelayanan Publik SIM Cak Bhabin terhadap Mutu Layanan dan Kepercayaan Masyarakat: Innovation of Public Service SIM Cak Bhabin towards Service Quality and Public Trust - Himawan, Agung - (Pusat Penelitian dan Pengembangan Polri, 2025)
The aim of this research is to describe the efforts of the Surabaya Police in improving the quality of public services and building public trust through the SIM Cak Bhabin Polrestabes Surabaya innovation. This study employs a qualitative method with a descriptive approach. The research uses innovation indicators outlined in the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 15 of 2015. Additionally, it applies indicators of consistency in maintaining services and products as proposed by Anggarsari (2022) and factors that contribute to public trust as identified by Mas'oed (2014). Data were collected through interviews, observations, documentation, and literature studies. The data analysis followed an interactive approach, consisting of data collection, data condensation, data presentation, and conclusion drawing. The findings indicate that the SIM Cak Bhabin Polrestabes Surabaya innovation program has been successfully implemented, aligning with the objectives of providing excellent public services. It has also contributed to increasing public trust and keeping up with technological advancements in the digital era. It is hoped that the SIM Cak Bhabin Polrestabes Surabaya innovation program will continue to operate consistently and sustainably with strong support from stakeholders.